Antropocentryczny wymiar życia gospodarczo-społecznego - Sobuś, ks. Paweł Bogumił (Annales. Etyka w Życiu Gospodarczym, 2009)
The Pastoral Constitution on the Church in the Modern World “Gaudium et Spes” says, “for man is the source, the center, and the purpose of all economic and social life” (63). Therefore, the man’s dignity has to be considered integrally in both his spiritual and bodily constitution and emphasized alongside his value and supernatural vocation. This enables attributing a special role to his transcendence in economic life. In their own productive activity, the possession and exchange of goods, a man should adhere to proper moral norms. However, what is observed is the incessant deepening of social inequalities in different parts of the earthly globe. Luxury accompanied by the wasting of goods adjoins indigence of people suffering a shortage of necessities. Thus it seems vital that economic institutions be established whose goal will be promoting good living conditions and an individual’s engagement in dignified economic activity and which will not destroy their human, moral and social dimension.